(untitled) (diségno, 2021)
The contribution is part of a broader research, aimed at the definition of analytical tools and languages based on codes of representation capable of describing the quality and welfare in cities, particularly in the context of the current declination and definitions of the terms vulnerability and resilience. Here are presented considerations on urban survey and on the predisposition of complex information systems for graphic analysis in particular contexts. The concept of resilience applied to the city can not ignore the specificity of places, a deep knowledge of the urban context, not only in its environmental, microclimatic and structural aspects, but also in those morphological and morphogenetic. The places of resilience are those places that, in continuous change, admit a rethinking. The contribution shows how the urban survey, in addition to being an opportunity for the representation of levels of analysis and knowledge of the built environment, can become a scientific tool capable of inducing a second and deeper level of analysis, related to different levels of knowledge, and become an efficient cause of a type of derived knowledge. Considering the conditions of resilience and sustainability, we recognize the need for dialogue at different scales of complexity, actors, skills, disciplines, intermediaries, and urban policies through common terrains of interchange that we have called graphic abacuses for the project.